Conditions that interfere with the Medicine students quality of life (Research, Society and Development, 2020)
The World Health Organization defines health as a state of physical, mental, and social well-being with the absence of any disease. However, even though this definition has already been consolidated among the world population, the definition of quality of life, the object of the present study, still needs to be defined. In recent years, there has been a growing concern about the quality of life in the training of health professionals, due to the high prevalence of anxiety and depression disorders in addition to other associated disorders among students in this area. Thus, the objective of the present study was to identify the main risk factors that interfere with the quality of life of medical students, as well as to explain what the mental disorders are prevalent in this population. This is an integrative literature review conducted with searches in the PubMed, SciELO and LILACS databases, based on the descriptors: depression, anxiety, quality of life, medical students, mental health. Works published in the last 10 years and articles relevant to this review were included. The results were divided according to the analyzed approaches: psychological, economic, social, and physical, in addition to including the analysis of the curricular influence on the students' quality of life. The psychological domain is a predominant concern among studies on the quality of life of medical students due to the increased prevalence of anxiety and depression disorders among this population. A high prevalence of anxiety disorders, depression and combined anxiety and depression was observed among students. In the economic domain, many students had difficulties at the beginning of their undergraduate course, which contributes to the need for assistance grants or loans to keep up with housing, transportation, and food. In the social domain, studies demonstrate the importance of the social component for quality of life, defined in subjective social parameters such as love, pleasure, happiness, personal fulfillment, and well-being. The physical domain stood out for the students' concern with physical activity and health, a great highlight was mainly the poor quality of these students in these items. Finally, regarding the curricular influence, there are solid complaints, mainly about the amount of content and the short time to learn it during training. Thus, the quality of life of Brazilian medical students is influenced by various spheres of daily life and the requirements of the course, still needs improvement, hampering the training of future doctors in the country.